Poverty and the Impact of COVID-19 : The Blue-Marble Health Approach - Hotez, Peter J. (Book collections on Project MUSE., 2020)
"While COVID-19 has ravaged global economies and changed the way of life for us all, the disease has a disproportionately devastating impact on poorer communities. For the millions without a job because of community shut downs, decisions about basic necessities and the fear of healthcare costs for those diagnosed with the novel coronavirus become critical. In these uncertain times, international diplomacy, solidarity, and cooperation are vital. Dr. Peter Hotez, dean of the National School of Tropical Medicine at Baylor College of Medicine, provides an essential look at the global issue of health and poverty through the lens of COVID-19. He introduces a new global paradigm known as 'blue marble health, ' through which he asserts that poor people living in wealthy countries account for most of the world's poverty-related illness. He explores the current state of neglected diseases in both China and the United States. By crafting public policy and relying on global partnerships to control or eliminate some of the world's worst poverty-related illnesses, Hotez believes, it is possible to eliminate life-threatening disease while at the same time creating unprecedented opportunities for science and diplomacy. Urgent, timely, and compassionate, this excerpted edition of Hotez's wide-sweeping Blue Marble Health serves as a timely guide for anyone committed to helping the millions of people who are facing the visceral threats of both poverty and COVID-19"--